THE SIGNIFICANCE OF RESPIRATORY AND ORTHOSTATIC TESTS IN DUPLEX SCANNING IN DIAGNOSTICS OF CELIAC ARTERY COMPRESSION SYNDROME - Bo Den; A. M. Ignashov; V. E. Perley; A. Yu. Gichkin; A. S. Ustyuzhaninov (Вестник хирургии имени И.И. Грекова)
The preoperative transabdominal ultrasonics duplex scanning (UDS) of celiac artery was made in quiet breathing, in inspiration, in expiration, using vertical position in 180 patients. As well as the intra-abdominal UDS was made before the decompression of the celiac artery using the pulmonary ventilation during narcosis and relaxation. Peak systolic blood velocity, degree of stenosis, arterial pressure gradient in the celiac artery and volume blood velocity were hemodynamically significant in quiet breathing, in expiration and intraoperatively, reliably lower in inspiration in vertical position. It is important to use respiratory and orthostatic tests in diagnostics of compressive stenosis of the celiac artery. The data, which were obtained in quiet breathing using vertical position, should be taken into account in order to distinguish the compressive stenosis from atherosclerotic stenosis or other origin.